2014
DOI: 10.2478/aopf-2014-0018
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid profiles in marine and freshwater fish from fish markets in northeastern Poland

Abstract: monounsaturated, 3.40-11.51% n-6 polyunsaturated, and 18.74-45.42% n-3 polyunsaturated acid. Marine fish contained significantly more Ón-3 PUFA (29.79%), EPA (12.26%), DHA (13.20%), and a higher n-3/n-6 (6.95) ratio than freshwater fish (13.13, 2.47, 7.14, 1.29%) (P £ 0.05). There were statistically significant differences in the n-3/n-6 ratio among fish species (cod (13.40) > sole (8.47) > flounder (4.30) > rainbow trout (2.41) > catfish (1.83) » salmon (1.63) > tilapia (0.57) » pangasius (0.36) (P £ 0.05)).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 16 publications
3
14
2
Order By: Relevance
“…Badiani et al [29] showed a higher SFA level in sturgeon (25.99%). Four fish species discussed in this study contained less SFA compared to other freshwater fish species like pike, zander, bream, tilapia, and pangasius, whose SFA level was between 36.28% and 42.18% [22,30]. Palmitic acid (C16:0) was the dominant SFA in the analyzed fish, from 10.50% in wels catfish up to 24.66% in grass carp, contributing 64.34%-78.61% of the total saturated fatty acid (SFA).…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Badiani et al [29] showed a higher SFA level in sturgeon (25.99%). Four fish species discussed in this study contained less SFA compared to other freshwater fish species like pike, zander, bream, tilapia, and pangasius, whose SFA level was between 36.28% and 42.18% [22,30]. Palmitic acid (C16:0) was the dominant SFA in the analyzed fish, from 10.50% in wels catfish up to 24.66% in grass carp, contributing 64.34%-78.61% of the total saturated fatty acid (SFA).…”
Section: Resultsmentioning
confidence: 76%
“…Palmitic acid (C16:0) was the dominant SFA in the analyzed fish, from 10.50% in wels catfish up to 24.66% in grass carp, contributing 64.34%-78.61% of the total saturated fatty acid (SFA). Palmitic acid was also found as the major SFA in the lipids of many freshwater fish species with percentage 16.83%-29.19% [22,30]. Stearic (C18:0) and myristic acid (C14:0) followed palmitic acid with regard to the quantity in the saturated fatty acid group determined in the fat of grass carp, bighead carp, wels catfish, and Siberian sturgeon.…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, fish are considered a very important source of n-3 polyunsaturated fatty acids (PUFA), especially eicosapentaenoic (EPA, C 20:5n-3) and docosahexaenoic (DHA, C 22:6n-3) [1,2]. Several clinical studies have demonstrated the relationship between n-3 PUFA intake and both the maintenance of physiological functions (optimal cardiovascular system, brain and vision functioning) and the prevention of certain health conditions (coronary artery disease and cancer), as well as the positive effects of n-3 PUFA consumption on some diseases (arthritis, hypertension, and diabetes mellitus) [3,4]. It is generally recognized that freshwater fish meat generally contains lower proportions of C 20, C 22, and n-3 PUFA but higher amounts of C 18 and n-6 PUFA, in particular 18:2n-6, than marine fish [5].…”
Section: Introductionmentioning
confidence: 99%
“…Higher pressure-resistance of proteolytic salmon enzymes compared to cod enzymes may be due to the protective effect of lipids. Salmon fl esh contains about 7%, and cod fl esh only 0.5-1% of lipids [Łuczyńska et al, 2014;Zeng et al, 2010]. In the available literature, there is no data on the activity of proteases in salmon fl esh as affected by pressure treatment.…”
Section: Fish Fl Eshmentioning
confidence: 93%